Toward an orofacial gene regulatory network. Issue 3 (17th September 2015) - Kousa, Youssef A.; Schutte, Brian C.
Abstract : Orofacial clefting is a common birth defect with significant morbidity. A panoply of candidate genes have been discovered through synergy of animal models and human genetics. Among these, variants in interferon regulatory factor 6 ( IRF6 ) cause syndromic orofacial clefting and contribute risk toward isolated cleft lip and palate (1/700 live births). Rare variants in IRF6 can lead to Van der Woude syndrome (1/35, 000 live births) and popliteal pterygium syndrome (1/300, 000 live births). Furthermore, IRF6 regulates GRHL3 and rare variants in this downstream target can also lead to Van der Woude syndrome. In addition, a common variant (rs642961) in the IRF6 locus is found in 30% of the world's population and contributes risk for isolated orofacial clefting. Biochemical studies revealed that rs642961 abrogates one of four AP‐2alpha binding sites. Like IRF6 and GRHL3, rare variants in TFAP2A can also lead to syndromic orofacial clefting with lip pits (branchio‐oculo‐facial syndrome). The literature suggests that AP‐2alpha, IRF6 and GRHL3 are part of a pathway that is essential for lip and palate development. In addition to updating the pathways, players and pursuits, this review will highlight some of the current questions in the study of orofacial clefting. Developmental Dynamics 245:220–232, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Orofacial clefting is a common birth defect with significant morbidity. An emerging orofacial gene regulatory network includes IRF6, GRHL3, TFAP2a and TP63. Further examination of this network may reveal the etiology of VWS, which will in turn illuminate iCLP. Despite our growing knowledge, targeted interventions to prevent orofacial clefting have not been developed.